2010
DOI: 10.1359/jbmr.091005
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic calcification on vertebral morphometry images predicts incident myocardial infarction

Abstract: Abdominal aortic calcification (AAC) measured on spine X-rays is an established risk factor for cardiovascular disease. We investigated whether AAC assessed using vertebral morphometry and a recently developed scoring system (AAC-8) is reliable and associated with cardiovascular risk factors or events. A total of 1471 healthy postmenopausal women and 323 healthy middle-aged and older men participated in 5 and 2 year trials of calcium supplements, respectively. AAC-8 was assessed on vertebral morphometry images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 27 publications
4
62
0
Order By: Relevance
“…(32) Furthermore, aortic calcification is associated with increased risk of myocardial infarction. (33,34) Taken together, these findings suggest that osteoporotic fractures may have a higher impact on subsequent AMI among women than among men. In contrast, a study by Varosy and colleagues reported that the risk of coronary events was lower in those who had postmenopausal fractures.…”
Section: Discussionmentioning
confidence: 85%
“…(32) Furthermore, aortic calcification is associated with increased risk of myocardial infarction. (33,34) Taken together, these findings suggest that osteoporotic fractures may have a higher impact on subsequent AMI among women than among men. In contrast, a study by Varosy and colleagues reported that the risk of coronary events was lower in those who had postmenopausal fractures.…”
Section: Discussionmentioning
confidence: 85%
“…(25) The mean baseline serum total calcium and phosphate concentrations and calcium-phosphate product were significantly higher in women with baseline AAC than in those without baseline AAC (p < .001, p ¼ .04, and p ¼ .003, respectively; Table 2). Figure 1 shows that, across quartiles of total serum calcium at baseline, the proportion of women with AAC increased linearly at baseline (p < .001) and at 5 years (p < .001).…”
Section: Womenmentioning
confidence: 95%
“…Full details of the method have been published previously, including details of the inter-and intrameasurer agreements. (25) Coronary calcium scores (CAC)…”
Section: Abdominal Aortic Calcification Scoringmentioning
confidence: 99%
See 2 more Smart Citations